Aluminum-lithium alloys : process metallurgy, physical metallurgy, and welding - Grushko, Olga; Ovsyannikov, Boris; Ovchinnikov, Viktor (Advances in metallic alloys ;, 2017)
This book provides theoretical foundations of the technological processes for melting, casting, forming, heat treatment, and welding of Al-Li alloys. It contains a critical survey of the research in the field and presents data on commercial Al-Li alloys, their phase composition, microstructure, and heat treatment of the ingots, sheets, forgings, and welds of Al-Li alloys. It is illustrated with examples of Al-Li alloy applications in aircraft structures and presents recommendations on solving practical problems involved with melting and casting ingots, welding of Al-Li alloys, and producing massive stampings for welded products.